O czym liście szumiały W czterdziestą rocznicę debiutu Donata Kirscha - Nowacki, Dariusz (Śląskie Studia Polonistyczne, 2017)
The article discusses circumstances surrounding Donat Kirsch’s debut (Liście croatoan, 1977) and presents various critical responses to the novel. A special attention is given to Jerzy Sosnowski who “demonized” Liście croatoan when in his journalistic writings and his novel (Sen sów, 2016) he underlined that the novel supposedly resists being read. The article attempts to reconstruct the inclinations of Kirsch’s book interpreters. It also raises the issue of literary skills that brought about this debut.